Quranic Linguistic Miracles: Fundamental Vocabularies and Their Impact on Arabic Language Studies - Zulkifli, Abdul Salam; Zolmaily, Muhammad Akmal; Talib, Noor Husna; Bahjat, Mujahid Mustafa; Mohd Ramli, Abdul Basir Awang (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Quran’s role as a foundational sacred text in preserving and shaping the Arabic language makes it an essential resource for linguists, learners, and educators to enhance their understanding of Quranic Arabic. A key sūrah that captures the fundamental vocabulary and concepts of the Qur’ān is Sūrah Al-Baqarah. Through a literature review, researchers found no previous study on the collection of these words and the number of derivatives in their various contexts. Therefore, this study aims to highlight the fundamental vocabulary of the Qurʼān in this Sūrah, as it includes these words that are repeated at least 50 times throughout the Qurʼān. Through the qualitative approach and analyzing documents in primary dictionaries of al-Quran words, researchers gathered data by analyzing the frequency of the words semantically and comparatively. They counted their frequency with their different derivations using